Heterogeneity found in the cagA gene of Helicobacter pylori from Japanese and non-Japanese isolates - Hoshino, Fuminori B.; Katayama, Kazuhiko; Watanabe, Kazuhiro; Takahashi, Shin-ichi; Uchimura, Hidemasa; Ando, Takao (Journal of gastroenterology, 2000)
We analyzed cagA genes from Helicobacter pylori strains isolated from Japanese and non-Japanese individuals for differences that could be associated with variations in virulence. The cagA genes from Japanese isolates (n = 12) and non-Japanese American Type Culture Collection (ATCC) strains (n = 4) were sequenced and compared with three published sequences. Phylogenetic analysis resolved two distinct clusters with a genetic distance of 0.1602. Similarity plot analysis of the amino acid sequences identified two highly variable regions of which each was unique to the Japanese and non-Japanese isolates, respectively. Furthermore, nucleic acid sequence analysis revealed that the multiple repeated sequences present in cagA may have been generated by homologous recombination and/or misaligned replication to promote variation in the cagA gene products. Our data indicate that alleic variations in the H. pylori genome exist between isolates from Japanese and non-Japanese subjects and that distinct H. pylori populations may be circulating in different geographical regions. Phylogenetic analysis did not reveal any association of a specific CagA type with a particular disease. Although extensive alterations were found in the cagA gene, none of the isolates contained a prematurely terminated CagA protein. The cagA gene may be advantageous to H. pylori, possibly by aiding its escape from host immune recognition by antigen modulation. Thus, this ability to elude the host immune system may contribute to an increased risk for gastric disease.